A systematic review of the influence of internal marketing on service innovation - Soheila Raeisi; Nur Suhaili Ramli; Meng Lingjie (Journal of Risk and Financial Management, 2020)
This paper aims aimed to present the trends of the literature review in internal marketing and service innovation between 1990 and 2016. The significant reason to conduct this research is that significant variables of internal marketing to link with service innovation are not clearly defined. This research yielded 22 systematic reviews of articles in the Scopus library and adopted a thematic analysis to analyze the data collected. This study provides provided answers to research questions by elaborating on overall trends, objectives, theoretical framework, methodologies, and potential variables that strongly connect between internal marketing and service innovation. While sample sizes are limited to this paper, it suggests suggested fruitful recommendations for future research to overcome this limitation. This research has had two practical implications for managers to redefine their roles and the relationship between members of the organization and to help managers and the firms to consider internal marketing efforts towards motivation, organizational culture, and organizational learning.
Keywords: 330; a systematic review; human resources; internal marketing; service innovation; thematic analysis